Notes to Reflect on a Political Ecology of Borderland Territories - Martha Moncada Paredes (Íconos)
By recognizing the improvement in geographies of extraction about territories that used to be considered marginal and subaltern until recently, such as the borderland regions, this article discusses, from the perspective of political ecology, the characteristics that this renewned pro-cess adopts in the borderland areas of Latin America. The internalization of the borderlands, the growth of the levels of security, and the cultural and social decline of these spaces are three characteristics of the new rediscovery of borderland territories, which impact sovereign-ty and the livelihood of the people who have been historically marginalized in these areas.